(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the treatment outcomes of E-psora and patient satisfaction in psoriasis at the FOB Dermatology Clinic in 2024. Methods: A cross-sectional study was conducted on 75 patients with mild to moderate plaque psoriasis treated at FOB Dermatology Clinic from January to October 2024. Treatment effectiveness was assessed using PASI and DLQI; satisfaction was measured with the Likert scale. Results: The mean PASI score significantly decreased from 6.97 to 2.13 (p<0.001). The proportions of patients achieving PASI50 and PASI75 were 76.9% and 38.5%, respectively. The DLQI score, reflecting quality of life, significantly improved from 7.26 to 4.52 after treatment. Adverse events were minimal, mainly erythema (15.5%) and mild pruritus (8.6%). Most patients were satisfied with the efficacy, safety, and convenience of treatment. Conclusion: E-psora demonstrated significant improvement in clinical symptoms of mild to moderate plaque psoriasis, enhanced quality of life with few adverse effects. The majority of patients were satisfied and willing to continue this treatment.